The Effect Of Video-Based Education On Adolescents' Knowledge About Anemia At SMP Negeri Satap 11 Mesuji In 2024 - Debby Sandela; Beniqna Maharani Besmaya; Septika Yani Veronica; Yunita Anggriani (Sean Institute, 2024)
The incidence of anemia is the most common problem found in adolescent girls. According to the World Health Organization (WHO), the prevalence of anemia among adolescent girls worldwide is still quite high, ranging from 40-88%, while in Indonesia, it is 21.7%. One of the factors causing anemia in adolescents is that adolescent girls with insufficient knowledge have a 4.998 times greater risk of not consuming iron supplement tablets compared to adolescent girls with adequate or good knowledge. To address adolescents' knowledge about anemia in adolescent girls, one action that can be taken is to provide education using videos. The use of video is a form of innovation in the development of educational media, especially by utilizing advanced technology such as animated videos. The purpose of this study is to determine the effect of video-based education on adolescents' knowledge about anemia. The research method is a pre-experiment with a one-group pre-post test design approach. The population in this study consists of all 184 female students at SMP Negeri Satap 11 Mesuji. The sampling technique uses purposive sampling with a total sample size of 65. This research was conducted at SMP Negeri Satap 11 Mesuji in September 2024. Data analysis uses the Wilcoxon test. The results of the study show that the average knowledge before being given education using video was 45.05 (less category), and the average after being given education was 79.08 (moderate category) with a p-value of 0.000 (p < 0.05), meaning that there is an effect of video-based education on adolescents' knowledge about anemia at SMP Negeri Satap 11 Mesuji in 2024. The suggestion in this study is that adolescent girls can utilize educational videos about anemia to increase their knowledge, especially about anemia. By increasing knowledge about anemia, it is hoped that adolescent girls can prevent and treat anemia from an early age.